FITNESS, a CCT domain-containing protein, deregulates reactive oxygen species levels and leads to fine-tuning trade-offs between reproductive success and defence responses in Arabidopsis - Osella, Ana Virginia (2018)
Environmental stresses are the major factors that limit productivity in plants. Here, we report on the function of an uncharacterized gene At1g07050, encoding a CCT domain-containing protein, from Arabidopsis thaliana. At1g07050 expression is highly repressed by oxidative stress. We used metabolomics, biochemical, and genomic approaches to analyse performance of transgenic lines with altered expression of At1g07050 under normal and oxidative stress conditions. At1g07050 overexpressing lines showed increased levels of reactive oxygen species (ROS), whereas knock-out mutants exhibited decreased levels of ROS and higher tolerance to oxidative stress generated in the chloroplast. Our results uncover a role for At1g07050 in cellular redox homeostasis controlling H2O2 levels, due to changes in enzymes, metabolites, and transcripts related to ROS detoxification. Therefore, we call this gene FITNESS. Additionally, several genes such as ACD6, PCC1, and ICS1 related to salicylic acid signalling and defence were found differentially expressed among the lines. Notably, FITNESS absence significantly improved seed yield suggesting an effective fine-tuning trade-off between reproductive success and defence responses.